Respuesta :

Answer:

x= -8

Step-by-step explanation:

First distribute: 3(2x+3)-x is equal to 6x+9-x, or 5x+9

Rewrite: 5x+9=x-23

Add 23 to both sides to get rid of it on one: 5x+32=x

Subtract 5x from both sides to get rid of it on one: 32= -4x

Divide by -4: -8=x

Tasyha

Answer:

x = -8

Step-by-step explanation:

[tex]3(2x + 3) - x = x - 23[/tex]

➡️ [tex]6x + 9 - x = x - 23[/tex]

➡️ [tex]5x + 9 = x - 23[/tex]

➡️ [tex]5x - x = - 23 - 9[/tex]

➡️ [tex]4x = - 32[/tex]

➡️ [tex]x = - 8[/tex] ✅

ACCESS MORE